The Immunoreactivity of Calbindin on Cerebellum Cortex and Hippocampus of Mice Brain After One Week Exposure To Radiofrequency Radiation. - Aryal, Bijay (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Radiofrequency radiation affects the calcium permeability and accordingly this induces pathophysiological changes in the brain and its subsequent output in the brain as tumor genesis, neural degeneration, and cognition or behavior changes. Hence, we investigated the effects of radiofrequency (RF) radiation on calcium binding proteins, reactive gliosis, and tumor genesis in mouse brain. Materials & Methods: Mice were exposed to radiofrequency radiation in the cage chamber with average specific absorption rate (SAR) of 1.6 W/kg and 4.0 W/Kg for one hour per day for five days. For histochemical studies, radiofrequency exposed brains were compared with sham control using calbindin D-28k antibody. Results: The immunoreactivity of calbindin D-28k, a marker for calcium homeostasis was found to increase in dose-response manner in hippocampus and cerebellar cortex. Conclusion: The short-term exposure to 835 MHz RF could induce disruption of calcium homeostasis and resulting neurobehavioral changes or brain tumor.